MicroRNA-194 regulates parasitic load and IL-1β-dependent nitric oxide production in the peripheral blood mononuclear cells of dogs with leishmaniasis. - Sidnei Ferro Costa; Matheus Fujimura Soares; Jaqueline Poleto Bragato; Marilene Oliveira Dos Santos; Gabriela Torres Rebech; Jéssica Henrique de Freitas; Valéria Marçal Felix de Lima (Public Library of Science (PLoS), 2024)
Domestic dogs are the primary urban reservoirs of Leishmania infantum, the causative agent of visceral leishmaniasis. In Canine Leishmaniasis (CanL), modulation of the host's immune response may be associated with the expression of small non-coding RNAs called microRNA (miR). miR-194 expression increases in peripheral blood mononuclear cells (PBMCs) of dogs with leishmaniasis with a positive correlation with the parasite load and in silico analysis demonstrated that the TRAF6 gene is the target of miR-194 in PBMCs from diseased dogs. Here, we isolated PBMCs from 5 healthy dogs and 28 dogs with leishmaniasis, naturally infected with L. infantum. To confirm changes in miR-194 and TRAF6 expression, basal expression of miR-194 and gene expression of TRAF6 was measured using qPCR. PBMCs from healthy dogs and dogs with leishmaniasis were transfected with miR-194 scramble, mimic, and inhibitor and cultured at 37° C, 5% CO2 for 48 hours. The expression of possible targets was measured: iNOS, NO, T-bet, GATA3, and FoxP3 were measured using flow cytometry; the production of cytokines IL-1β, IL-4, IL-6, IL-10, TNF-α, IFN-γ, and TGF-β in cell culture supernatants was measured using capture enzyme-linked immunosorbent assays (ELISA). Parasite load was measured using cytometry and qPCR. Functional assays followed by miR-194 inhibitor and IL-1β blockade and assessment of NO production were also performed. Basal miR-194 expression was increased in PBMC from dogs with Leishmaniasis and was negatively correlated with TRAF6 expression. The mimic of miR-194 promoted an increase in parasite load. There were no significant changes in T-bet, GATA3, or FoxP3 expression with miR-194 enhancement or inhibition. Inhibition of miR-194 increased IL-1β and NO in PBMCs from diseased dogs, and blockade of IL-1β following miR-194 inhibition decreased NO levels. These findings suggest that miR-194 is upregulated in PBMCs from dogs with leishmaniasis and increases parasite load, possibly decreasing NO production via IL-1β. These results increase our understanding of the mechanisms of evasion of the immune response by the parasite and the identification of possible therapeutic targets.